Suitability and Transferability of the Resource-Based Habitat Concept: A Test With an Assemblage of Butterflies - Turlure, Camille; Schtickzelle, Nicolas; Dubois, Quentin; Baguette, Michel; Dennis, Roger L. H.; Van Dyck, Hans (Frontiers in Ecology and Evolution, 2019)
A functional definition of the habitat-concept based on ecological resources incorporates three interconnected parameters: composition, configuration and availability of the resources. The intersection of those parameters represents the functional habitat of a given population or species. Resource composition refers to the co-occurrence of the resources required by each individual to complete its life cycle. Resource configuration refers both to the way individual resources are spatially distributed within the habitat and the way all the resources are organized in the habitat space. Resource availability refers to the accessibility and procureability of resources. Variation in these variables is predicted to influence the demography of the population. To test the suitability of this definition and its transferability across landscapes, we first conducted a very detailed study on habitat and resource use of five butterfly species within a large nature reserve. Second, we conducted a larger-scale study, focusing on metapopulations of two species. We monitored demography for each species and tested whether its variation can be explained by (1) the vegetation type, (2) the vegetation composition or (3) the availability and configuration of the species-specific ecological resources. To confirm that resource availability and configuration reflect habitat quality, we also assessed their impacts on individual morphology. Whatever the investigated spatial scale, our results quantitatively demonstrate the overall better performance of the resource-based habitat approach compared to other most commonly used approaches. Our analysis allowed us to assess the relative importance of each ecological resource in terms of both their availability and organization relative to the species’ abundance, demography and individual fitness measures. Resource availability did not play the predominant role in defining habitat quality as it was in most cases overruled by resource organization. Finally, we confirmed the between-population transferability of the habitat definition and quality estimates while adopting a resource-based habitat approach. Our study clearly demonstrates the suitability of the resource-based definition of the habitat. Therefore, we argue that this approach should be favored for species of conservation concern. Although most conclusions so far have emerged from butterfly studies, the resource-based definition of the habitat should also be ecologically relevant to many other organisms.